Evaluation of the Effect of Soil Pollution of Savar Areas and Fertilizer Management on Yield and Nutrient Accumulation in Tomato (Solanum lycopersicum L.) - Shamsuzzoha, Md.; Khan, M. A.; Amin, A. K. M. Ruhul; Sumon, Mahmud Hossain; Paul, Alok Kumar; Sultana, Mst. Sharmin; Alam, Ishrat (International Journal of Economic Plants, 2026)
A field experiment was conducted from November, 2022 to April, 2023 in industrially contaminated soils of Savar, Bangladesh, using a Randomized Complete Block Design with four treatments: T0 (Control), T1 (100% recommended chemical fertilizer), T2 (75% chemical+25% cow dung), and T3 (50% chemical+50% cow dung), replicated four times. Growth parameters, yield attributes, fruit yield, and nutrient accumulation were recorded following standard procedures. Soil pollution substantially restricted plant vigor and yield under T0, while fertilizer application significantly improved tomato growth and productivity. The integrated treatments (T2 and T3) outperformed T1 in most parameters. T3 produced the highest fruit yield, increased fruit dry matter content, and enhanced plant biomass accumulation, demonstrating improved nutrient uptake efficiency despite the polluted soil environment. The combined organic–inorganic nutrient management mitigated the adverse effects of industrial contaminants more effectively than chemical fertilizer alone. The findings indicate that INM helped optimize nutrient availability, improve soil biological activity, and support physiological functions necessary for yield enhancement. Integrated nutrient management, particularly T3, effectively improved tomato productivity and nutrient enrichment in industrially polluted soils of Savar. The study provides evidence that replacing 50% chemical fertilizer with cow dung can enhance yield resilience under contaminated soil conditions. This approach may serve as a sustainable fertilizer strategy for safe and productive vegetable cultivation in polluted agro-ecosystems.